(3GdhGQOGJs - (3GdTjN eMeO YHOg , eMeO YHOg Hf MSf NjQ Gddg GdJQceGfj,J (B1323 (3g` s
(3ChdgG (B:s
(3CeG HYO , ajbhd eMeO YHOg aHjfeG CfG Mhd GdQjGV CMhe EP YKQJ s
(3BNQgG (B:s
(3aGddg aGYd ef MjK GdYHO aGYd hGdYHO aGYd ef MjK GdQH aGYd hGdhLhO ai LejY eQGJHg eNJGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B252 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B272s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3MceI JjehQ (B147) s
Keywords: (3GdadSaI hGdefWbs